Roman law and modern national systems of civil procedure: metamorphoses of harmonization of the civil process within the framework of European and Eurasian integration - Nadezhda V. Sukhova (Правоприменение)
The subject. This article is devoted to the discussion of transformation of civil justice within the framework of European and Eurasian integration in the context of globalization. Globalization has been often mistakenly treated as a sociocultural process of establishing unity of humanity. But in the author’s opinion globalization is an information – economic megatrend. We can find a precise characterization of modern globalization process in definition “glocalization” by British sociologist R.Robertson which is understood as connection between global and local processes.The article means “glocalization” as  globalization of economic and localization of cultures. The author also tries to synthesize some trends in the development and convergence of civil procedural law in Europe and in post-Soviet space making attempts to find some unity in the diversity of transformations.Methodological bases of research are General scientific methods (dialectics, analysis, synthesis, comparison); private and scientific methods (interpretation, formal-logical, comparative-legal, based on the actual approach).The aims of the article are: to analyze the reasons and factors that influence the convergence of the civil process in the framework of European and Eurasian integration; to identify gaps in legal regulation, difficulties encountered in the activities of courts in the implementation of justice; to identify trends in the further development of the civil process within the framework of European and Eurasian integration.The main scientific results. The basis of social integration and mutual understanding has its roots at least in the countries of continental Europe in common source, in the Roman-canonical models that formed the “procedural order of communication”  for many European countries before the codification period.The civil procedure systems of modern states are facing unprecedented challenges today. In accordance with contemporary and historical comparative analysis fundamental reforms are condition for surviving of civil courts as protectors of human rights lied in the base of modern jurisdictions. Moreover, the reforms indicate common tendency of nations to communication on the base of unity in diversity of changes. The landscape of civil justice in Europe and Eurasia shows unity and diversity of processes in legal sphere.Conclusions. The reasons and factors that influence the convergence of the civil process in the framework of European and Eurasian integration were identified. The main trend of development is to solve the unprecedented problems that the civil procedural systems of modern states face today.